Transformasi Proses Penyidikan Oleh Kepolisian Berdasarkan Perspektif Sistem Peradilan Pidana - Ayu Putriyana; Yuliana (Jurnal Penelitian Hukum De Jure, 2026)
Reforms in criminal justice system policies are a fundamental basis for Indonesian society, because previous policies are no longer relevant to current legal phenomena. This article analyzes the transformation of the investigation process by comparing the regulations in the 1981 Criminal Procedure Code (KUHAP) and the New Criminal Procedure Code (KUHAP), and examines the challenges of their implementation. This research uses a normative juridical research method with a descriptive qualitative approach, conducted through a literature review of regulations, doctrines, and relevant legal literature. The research results show that the reform of the Criminal Procedure Code (KUHAP) brings significant paradigm shifts toward due process of law, including the affirmation of a minimum standard of two pieces of evidence in the determination of suspects, the strengthening of suspects' rights from the early stages of investigation, the obligation of legal assistance, the expansion of oversight mechanisms, and the recognition of electronic evidence. However, implementing the new Criminal Procedure Code faces various challenges, including regulatory disharmony, limitations in implementing regulations, the readiness of institutions and law enforcement officers, and disparities in technological resources across regions. Therefore, the success of the investigation transformation highly depends on the consistency in officers, the formulation of derivative regulations, strengthening law enforcement officers' capacity, and changing the legal culture so that procedural justice can be effectively realized.